2014
DOI: 10.1177/0194599814521013
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Otoprotection of Metformin in Radiation‐Induced Sensorineural Hearing Loss in the Guinea Pig

Abstract: Metformin is not ototoxic or radioprotective in vitro or in vivo. Ears solely subjected to metformin had better hearing thresholds than the rest of the groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“… 2 , 3 , 4 , 5 , 6 Regulators, such as p53, reactive oxygen species and c-Jun N-terminal kinases are known to have important roles in apoptosis of irradiated hair cells. 7 , 8 , 9 , 10 N -acetylcysteine, 11 epicatechin 10 and metformin 12 have been previously demonstrated to be effective in reducing apoptosis in irradiated hair cells. Because studies have been limited, the mechanisms underlying IR-induced auditory cell death remain unclear and require further investigation.…”
mentioning
confidence: 99%
“… 2 , 3 , 4 , 5 , 6 Regulators, such as p53, reactive oxygen species and c-Jun N-terminal kinases are known to have important roles in apoptosis of irradiated hair cells. 7 , 8 , 9 , 10 N -acetylcysteine, 11 epicatechin 10 and metformin 12 have been previously demonstrated to be effective in reducing apoptosis in irradiated hair cells. Because studies have been limited, the mechanisms underlying IR-induced auditory cell death remain unclear and require further investigation.…”
mentioning
confidence: 99%
“…Metformin on its own was not found to be ototoxic. 88 Decades of clinical use have demonstrated that metformin is generally well-tolerated and safe even in prediabetics as a preventative agent. 48 Adverse effects, when they occur, are generally gastrointestinal in origin.…”
Section: Resultsmentioning
confidence: 99%
“…Guinea pig in vivo model for fractionated radiation ototoxicity also demonstrated HL in the higher frequencies (22)(23)(24). Although the molecular mechanisms behind HL for fractionated radiation likely differ than for single-fraction radiation ototoxicity, both types of radiation exposure preferentially affect the basal turn of the cochlea, suggesting that the apical and middle turns are more resilient than the basal turn to radiation injury.…”
Section: Discussionmentioning
confidence: 98%